Development and research of generalized computer model of electric drive with pulse-phase control of angular velocity - A. V. Bubnov; A. N. Chetverik; A. N. Chudinov (Омский научный вестник)
The article presents a generalized computer model of electric drive with pulse-phase control of angular velocity. The model is created on the basis of the pulsed frequency-phase discriminator model with additional functionality that allows to investigate the most effective, from the point of view of improvement of dynamic indicators of quality of regulation, ways of management of the given electric drive. This significantly reduces the simulation time, which accelerates the study of synchronous-common-mode electric drive and phase-locked electric drive in the high speed areas.